Effect of Different Chronotype on Comorbidity and Resistance to Psycho-Emotional Stress in Hypertension Associated With Hepato-Biliary Pathology in the North - EV, Sevostyanova; VI, Hasnulin (Journal of Diseases, 2014)
Study of the alien inhabitants of the North - hypertensive patients with concomitant pathology of the hepato-biliary system, depending on morning or evening chronotype showed greater severity of comorbidity of hypertension and pathology of the hepato-biliary system in patients with morning chronotype. Psychophysiological analysis revealed higher level of psycho-emotional stress accompanied by violation of psychophysiological functions, important in disturbances of adaptation to natural factors and the increase in the degree of desynchronosis in patients with morning chronotype. The greater resistance to psycho-emotional stress in patients living in the North of evening chronotype was revealed.